Hyperpolarization-Activated Cyclic Nucleotide-Gated Non-selective (HCN) Ion Channels Regulate Human and Murine Urinary Bladder Contractility - Mader, Felix; Müller, Steffen; Krause, Ludwig; Springer, Armin; Kernig, Karoline; Protzel, Chris; Porath, Katrin; Rackow, Simone; Wittstock, Tristan; Frank, Marcus; Hakenberg, Oliver W.; Köhling, Rüdiger; et al. (Frontiers in Physiology, 2018)
Purpose: Hyperpolarization-activated cyclic nucleotide gated non-selective (HCN) channels have been demonstrated in the urinary bladder in various species. Since they play a major role in governing rhythmic activity in pacemaker cells like in the sinoatrial node, we explored the role of these channels in human and murine detrusor smooth muscle. Methods: In an organ bath, human and murine detrusor smooth muscle specimens were challenged with the HCN channel blocker ZD7288. In human tissue derived from macroscopically tumor-free cancer resections, the urothelium was removed. In addition, HCN1-deficient mice were used to identify the contribution of this particular isoform. Expression of HCN channels in the urinary bladder was analyzed using histological and ultrastructural analyses as well as quantitative reverse transcriptase polymerase chain reaction (RT-PCR). Results: We found that the HCN channel blocker ZD7288 (50 µM) both induced tonic contractions and increased phasic contraction amplitudes in human and murine detrusor specimens. While these responses were not sensitive to tetrodotoxin, they were significantly reduced by the gap junction inhibitor 18β-glycyrrhetic acid suggesting that HCN channels are located within the gap junction-interconnected smooth muscle cell network rather than on efferent nerve fibers. Immunohistochemistry suggested HCN channel expression on smooth muscle tissue, and immunoelectron microscopy confirmed the scattered presence of HCN2 on smooth muscle cell membranes. HCN channels seem to be down-regulated with aging, which is paralleled by an increasing effect of ZD7288 in aging detrusor tissue. Importantly, the anticonvulsant and HCN channel activator lamotrigine relaxed the detrusor which could be reversed by ZD7288. Conclusion: These findings demonstrate that HCN channels are functionally present and localized on smooth muscle cells of the urinary bladder. Given the age-dependent decline of these channels in humans, activation of HCN channels by compounds such as lamotrigine opens up the opportunity to combat detrusor hyperactivity in the elderly by drugs already approved for epilepsy.